The Long Thirties (1929–1945) – Conceptual Approaches to the Transformation of Modernity - Rákosník, Jakub (Dějiny – teorie – kritika, 2010)
This study examines the thesis of the long 1930s. The theory of modernization diagnoses separate phases of modernity. Th e 1929-1945 period saw the culmination of what is known as the stage of organized modernity, which followed on to some extent from 19th century liberal modernity. This transformation process started in the last third of the 19th century and came to a head as a result of the great crash and the Second World War. From this standpoint the 1929-1945 period forms a unit in which the preconditions are formed for the creation of a postwar universalist welfare state and a mixed economy. The key processes here were an increase in state intervention in the economy and the promotion of social rights as a result of the experience of mass unemployment and wartime collectivism.